OPTIMALISASI KENYAMANAN THERMAL RUANG BACA BANGUNAN PERPUSTAKAAN R.M SOEDJONO DJOJOHADIKUSUMO - Muhammad Fauzan; Agung Prapsetyo; M. Zain Triputra; Budi Mawardi Syam (JURNAL TEKNIK SIPIL PERTAHANAN, 2023)
The Military Academy is an educational institution located in the City of Magelang, Central Java. The facilities provided at educational institutions are very diverse, including the library building, the library has a reading room for cadets to carry out learning or parenting activities. In order to increase the comfort of library visitors there is a thermal comfort factor. The purpose of this research is to find out which indicators of thermal comfort in the reading room are optimal and how to optimize the maintenance and repair of public facilities in the library reading room. This research is a mixed method research. The data sources in this study were primary data obtained through in-depth interviews with library administrators and visitors, Kazi Akmil, documentation and observation of facilities in the library reading room and distributing questionnaires to respondents, namely Cadets TK III. While secondary data comes from literature and journals that support the completion of this Final Project, with reduction analysis and the Likert method in the discussion. The results of this study are that the maintenance and repair of the reading room facilities at the R.M Soedjono Djojohadikusumo Library are in good condition and ready to be used to carry out the learning process or care for the reading room